What is the impact of the use of transanastomotic feeding tube on patients with esophageal atresia: a systematic review and meta-analysis - Chuan Wang; Liwei Feng; Yanan Li; Yi Ji (BMC, 2018)
Abstract Background The transanastomotic feeding tube (TAFT) is widely used around the world in patients with esophageal atresia (EA). However, the safety of the use of TAFT is still unknown and remains to be clarified. Methods The following electronic databases were searched: PubMed, EMBASE and Cochrane. Studies comparing outcomes in patients with the use of TAFT (TAFT+) and patients without the use of TAFT (TAFT-) were scrutinized. The quality of included studies was evaluated with the Newcastle-Ottawa scale score. Statistical heterogeneity was assessed using the I 2 value. A fixed or random-effect model was applied. Results Four retrospective controlled studies involving 455 patients were included. The pooled estimates showed that the use of TAFT significantly increased the risk of stricture, with a risk ratio (RR) of 1.83 (95% CI 1.30-2.58; P = 0.0005). The meta-analyses of other postoperative complications did not show significant differences between TAFT+ and TAFT- group, with a RR of 1.65 (95% CI 0.93-2.93; P = 0.09) for anastomotic leakage, 0.91 (95% CI 0.34-2.44; P = 0.85) for sepsis, 1.89 (95% CI 0.22-16.20; P = 0.56) for tracheomalacia, 0.50 (95% CI 0.13-1.93; P = 0.31) for gastroesophageal reflux, 1.29 (95% CI 0.28-5.92; P = 0.74) for wound infection, and 0.97 (95% CI 0.03-36.75; p = 0.99) for pneumonia. Conclusions This study demonstrates that the use of TAFT in patients with EA significantly increases the risk of stricture. However, TAFT is not associated with other complications, including anastomotic leakage, sepsis, tracheomalacia, gastroesophageal reflux, wound infection and pneumonia.